Dlx5/6-Enhancer Directed Expression of Cre Recombinase in the Pharyngeal Arches and Brain - Ruest, Louis-Bruno (2003)
Dlx5 and Dlx6, two members of the Distalless gene family, are required for development of numerous tissues during embryogenesis, including facial and limb development. This gene pair is expressed in tandem, transcribed toward each other and separated by a short intergenic region containing multiple putative enhancers. Targeted inactivation of Dlx5 and Dlx6 in mice results in multiple developmental defects in craniofacial and limb structures, suggesting that these genes are crucial for aspects of both neural crest and nonneural crest development. To further investigate potential developmental roles of Dlx5 and Dlx6, we used one of the Dlx5/6 intergenic enhancers to drive Cre recombinase expression in transgenic mice. Crossing Dlx5/6-Cre transgenic mice with mice from the R26R strain results in β-galactosidase staining in the apical ectodermal ridge, brain, and neural crest-derived mesenchyme of the pharyngeal arches, with staining in term embryos observed in the facial skeleton and specific brain structures. However, in contrast to endogenous expression patterns of Dlx5 and Dlx6, Cre expression within the pharyngeal arches occurs during a very narrow window in early development. Our studies suggest that Dlx5/6-Cre mice may prove useful both in further understanding the function and regulation of Distalless genes during development and in studies of gene function in conditional knockout mice.